Practical open source software for libraries - Engard, Nicole C., 1979- (Chandos information professional series., 2010)
Open source refers to an application whose source code is made available for use or modification as users see fit. This means libraries gain more flexibility and freedom than with software purchased with license restrictions. Both the open source community and the library world live by the same rules and principles. Practical Open Source Software for Libraries explains the facts and dispels myths about open source. Chapters introduce librarians to open source and what it means for libraries. The reader is provided with links to a toolbox full of freely available open source products to use in their libraries. Provides a toolbox of practical software that librarians can use both inside and out of the libraryDraws on the author's wide-ranging practical experience with open source software both in and out of the library communityIncludes real life examples from libraries and librarians of all types and locations.